Evaluation of Recombinant Attenuated Salmonella Vaccine Strains for Broad Protection against Extraintestinal Pathogenic Escherichia coli - Maddux, Jacob T.; Stromberg, Zachary R.; Curtiss III, Roy; Mellata, Melha (Frontiers in Immunology, 2017)
Antibiotic-resistant bacterial infections are difficult to treat, producing a burden on healthcare and the economy. Extraintestinal pathogenic Escherichia coli (ExPEC) strains frequently carry antibiotic resistance genes, cause infections outside of the intestine, and are causative agents of hospital-acquired infections. Developing a prevention strategy against this pathogen is challenging due to its antibiotic resistance and antigenic diversity. E. coli common pilus (ECP) is frequently found in ExPEC strains and may serve as a common antigen to induce protection against several ExPEC serotypes. In addition, live recombinant attenuated Salmonella vaccine (RASV) strains have been used to prevent Salmonella infection, but can also be modified to deliver foreign antigens. Thus, the objective of this study was to design a RASV to produce ECP on its surface and assess its ability to provide protection against ExPEC infections. To constitutively display ECP in a RASV strain, we genetically engineered a vector (pYA4428) containing aspartate-β-semialdehyde dehydrogenase and E. coli ecp genes and introduced it into RASV 9558. RASV 9558 containing an empty vector (pYA3337) was used as a control to assess protection conferred by the RASV strain without ECP. We assessed vaccine efficacy in in vitro bacterial inhibition assays and mouse models of ExPEC-associated human infections. We found that RASV 9558(pYA4428) synthesized the major pilin (EcpA) and tip pilus adhesin (EcpD) on the bacterial surface. Mice orally vaccinated with RASV 9558(pYA3337) without ECP or 9558(pYA4428) with ECP, produced anti-Salmonella LPS and anti-E. coli EcpA and EcpD IgG and IgA antibodies. RASV strains showed protective potential against some E. coli and Salmonella strains as assessed using in vitro assays. In mouse sepsis and UTI challenge models, both vaccines had significant protection in some internal organs. Overall, this work showed that RASVs can elicit an immune response to E. coli and Salmonella antigens in some mice, provide significant protection in some internal organs during ExPEC challenge, and thus this study is a promising initial step towards developing a vaccine for prevention of ExPEC infections. Future studies should optimize the ExPEC antigens displayed by the RASV strain for a more robust immune response and enhanced protection against ExPEC infection.